PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN LKPD TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV GUGUS III KECAMATAN TANJUNG MUTIARA - Lesni; Inge Angelia; Sidik Puryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic mathematics learning in elementary schools often remains teacher-centered and outcome-oriented, limiting students’ critical thinking and conceptual understanding. This study aims to examine the effect of applying the Discovery Learning model assisted by Student Worksheets (LKPD) on critical thinking skills and mathematics learning outcomes of fourth-grade students in Gugus III, Tanjung Mutiara District. The research employed a quantitative approach with a quasi-experimental design, involving an experimental class using Discovery Learning with LKPD and a control class using conventional methods. The sample consisted of 47 students: 24 in the experimental class (SDN 21 Durian Kapeh) and 23 in the control class (SDN 08 Durian Kapeh). Research instruments included critical thinking tests, learning outcome tests, and student response questionnaires. Data were analyzed using MANOVA after fulfilling normality and homogeneity assumptions. The results indicated that Discovery Learning assisted by LKPD had a significant effect on critical thinking skills (19.1%) and learning outcomes (25.7%), with a simultaneous contribution of 29.6%. These findings demonstrate that the Discovery Learning model assisted by LKPD is more effective than conventional methods in enhancing conceptual understanding and promoting higher-order thinking skills. Therefore, this model aligns with Bruner’s constructivist theory and the Merdeka Curriculum’s emphasis on active, contextual, and student-centered learning.